(untitled) (Dhaka University Journal of Business Studies, 2023)
The goal of this paper is to investigate the influences of green Human Resousce Managent practices on employee work performance. In order to improve the utilization of resources, performance-oriented components are indispensable. In this sense, the study focuses on five components of green HRM practices i.e., green job design, green HR planning, green recruitment and selection, green training and development, and green compensation that have contributory effect on employee work performance. A total of 384 respondents were selected and data has been collected through structured questionnaire from the samples who are the permanent employees of two largest telecommunication service companies in Bangladesh. For data input SPSS version-20 and for analysis structural equation modeling software Smart-PLS (version- 3) have been utilized. Results show that all five components of green HRM activities have significant positive impact on employee work performance. Thus, this research contributes to broadening the profound insights of green HRM practices to explore the ecological execution of companies by employee performance. Journal of Business Studies, Vol. XLII, No. 2, August 2021 Page 113-137